THE DAMAGE OF THE OPTIC NERVE AS THE OUTCOME OF UNINTENTIONAL POISONING BY CLOSANTEL - Kurakina, Evgenia Sergeevna; Ioyleva, Elena Eduardovna; Saif, Mutlaq Ali Saif; Gavrilova, Natalia Alexandrovna (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2021)
Background: In recent decades, the problem of toxic damage of the visual system due to poisoning by various medicines has become particularly relevant. The clinical case of a bilateral acute optic neuropathy of toxic genesis in a patient by the unintentional application of closantel used in veterinary practice is presented in the report. Closantel is a structural derivative of the salicylanilides, which is used exclusively in veterinary medicine for the prevention and treatment of large and small-scale cattle. Neurological and ophthalmic symptoms are often associated with the intoxication of closantel.Objective: To describe the toxic damage of the optic nerve due to unintentional poisoning by closantel.Methods: A patient aged 55 years is examined. A standard survey of ophthalmology was carried out. Photoregistration of the ocular fundus was used by a funduscamera Visucam 500 (Carl Zeiss Meditec AG, Germany), from special methods of research - the spectral optical coherence tomography (OCT) with a study of the macular area of the retina and the disc of the optic nerve on the device Zeiss Cirrus 5000 (Carl Zeiss Meditec, USA) and the optical coherence tomography with the function of angiography (OCT-A) of the macular area of the retina using RTVue XR Avanti (Optovue, USA)Results: The patient complained of a severe, yet painless, reduction in vision of both eyes after an accidental intramuscular injection of the medicine called